Research Progress on the Mechanism Between Polycystic Ovary Syndrome and Abnormal Endometrium - Xue, Zhu; Li, Juanli; Feng, Jiaxing; Han, Han; Zhao, Jing; Zhang, Jiao; Han, Yanhua; Wu, Xiaoke; Zhang, Yuehui (Frontiers in Physiology, 2021)
As a highly dynamic tissue, the endometrium is periodically shed in response to the secretion of estrogen and progesterone. After menarche, the endometrium of healthy women proliferates and differentiates under the action of steroid hormones (e.g., 17β-estradiol and progesterone) that are secreted by the ovaries to provide appropriate conditions for embryo implantation. Polycystic ovary syndrome (PCOS), a prevalent endocrine and metabolic disorder in reproductive-aged women, is usually associated with multiple cysts within the ovaries and excess levels of androgen and is characterized by hirsutism, acne, menstrual irregularity, infertility, and increased risk of insulin resistance. Multiple factors, such as anovulation, endocrine-metabolic abnormalities, and inflammation, can disrupt the endometrium in PCOS patients and can lead to endometrial hyperplasia, pregnancy complications, or even cancer. Despite many recent studies, the relationship between PCOS and abnormal endometrial function is still not fully understood. In this review, we investigate the correlation of PCOS patient endometrium with anovulation, hyperandrogenemia, insulin resistance, progesterone resistance, and inflammatory cytokines, aiming to provide a theoretical basis for the treatment of disorders caused by endometrial dysfunction in PCOS patients.